Limiting efficiency of OLS vs. GLS when regressors are fractionally integrated - Walter Krämer; Uwe Hassler (Universität Dortmund, Sonderforschungsbereich 475 - Komplexitätsreduktion in Multivariaten Datenstrukturen, 1997)
We show that previous results on the asymptotic efficiency of OLS versus GLS in the context of trending data carry over to regressors of the fractionally integrated type.
Keywords: 519